ACEPHATE INDUCED ALTERATIONS IN Mg TIONS IN Mg2+ ATPASE AND Na ASE AND Na+ K+ ATPASES OF DIFFERENT BRAIN REGIONS OF ALBINO RATS - S. SIRAJ MOHIYUDDIN,; S. RAJESWARA REDDY,; L. ANANDA KUMAR,; P. JACOB DOSS, (The Bioscan, 2009)
Organophosphate Compounds are the most widely used group of insecticides in the world. Acephate (o, s, dimethyl acetyl phosphoramidothioate) is a recemic organophosphorus insecticide and is effective against a wide range of insects and their larvae. The present study investigated the effect of acute sublethal dose of Acephate on Mg2+ and Na+ K+ ATP ases activity in different regions of rat brain viz., Cerebral cortex, Hippocampus, Cerebellum, and Medulla oblongata. The LD50 of Acephate (1080mg/kg BW) was evaluated by probit analysis method of Finney. Albino rats were divided into 4 groups with group I serving as control, where as II, III and IV groups were given (1/5LD50 i.e., 216mg/kgbw) orally single, double, and multiple doses of Acephate respectively. After stipulated time period the rats were sacrificed and the brain tissues were isolated at cold conditions to carry out estimations of Mg2+ATPase and Na+ K+ATP ase activity. The decrease in the activity of these enzymes was in dependent manner.